Exploring the influences of myopia in primary and secondary school students in Xinjiang using propensity score matching - Hu, Xiaopeng; Yuan, Xianyan; Li, Hua; Gong, Haoxuan; Fu, Zhicong; Xie, Yuting; Zhu, Lin; Chen, Haina; Yang, Yingli; Rui, Dongsheng (Frontiers in Medicine, 2025)
ObjectiveDue to the high prevalence of myopia among primary and secondary school students in Shihezi City in recent years, this study was conducted to understand the prevalence and the factors influencing it and to provide a scientific basis for future interventions to improve, protect, and promote the visual health of these students.MethodsThe study population consisted of primary and secondary school students in Shihezi City. Stratified random sampling was employed for participant selection. Schools were first randomly chosen from both urban and rural areas of Shihezi City, followed by grade-level stratification within each selected school. Two classes per grade were randomly designated as sample classes. All students underwent vision screening. Students in Grade 4 and above completed questionnaires to investigate myopia-associated factors. To control for confounding effects, four variables–grade level, gender, urban/rural residence, and parental myopia status–were matched and analyzed using propensity score matching.ResultsA total of 6,732 individuals were surveyed in this study, with 6,092 ultimately included (participation rate: 90.49%), of whom boys represented 51.10%. The overall prevalence of myopia was 59.55%. The prevalence of myopia in urban areas was 68.17%, while in rural areas, it was 42.42%, a difference that was statistically significant. Risk factors for myopia included being female, having myopic parents, engaging in close-distance reading or writing, sleeping less than 8 h per night, and receiving education at an older age. Protective factors against myopia included attending school in a rural area, watching television from a distance of more than 3 m, and having had a vision examination at least once in the past year.ConclusionThe myopia rates in Shihezi City exceed the national average and show a gradual increase with advancing school age. In addition to inherent factors such as gender, receiving education at an older age, and genetic predisposition, myopia prevention strategies should include proper sitting posture, good eye habits, and health promotion measures.